Comparison of Sonographically Guided Core Needle Biopsy and Excision in Breast Papillomas: Clinical and Sonographic Features Predictive of Malignancy. (1st February 2013) - Sohn, Yu-Mee; Park, So Hyun
Abstract : Objectives: The aim of this study was to evaluate the clinical factors and sonographic features of benign papillomas of the breast proven by sonographically guided 14‐gauge core needle biopsy and their upgrade or malignancy rate after sonographically guided vacuum‐assisted excision or surgical excision. Methods: We reviewed the medical records of patients who underwent core needle biopsy from July 2005 to December 2011. We evaluated 39 benign papillomas without atypia in 34 patients. The papillomas were diagnosed by core needle biopsy and underwent surgical or vacuum‐assisted excision. After core needle biopsy, imaging‐histologic correlation was performed to determine concordance. The upgrade and malignancy rates were assessed after surgical or vacuum‐assisted excision, and associated clinical and radiologic factors, including patient age, lesion size, distance from the nipple, sonographic features, and American College of Radiology Breast Imaging Reporting and Data System (BI‐RADS) category were evaluated. Results: Three lesions (7.7 %) among 39 papillomas were upgraded to papilloma with atypia after surgical excision. There was no malignancy after excision. The upgrade rates for BI‐RADS categories 3, 4a, 4b, and 4c were 0%, 6.9%, 0%, and 20%, respectively. There were no significant differences in the upgrade to papilloma with atypia in terms of the presence of symptoms, lesion size, distance from the nipple, BI‐RADS category, or imaging‐histologic correlation. Conclusions: Prediction of papilloma with atypia, not malignancy, was challenging because there were no associated clinical or radiologic factors to predict papilloma with atypia before excision. However, there was no malignancy after excision. Therefore, intensive surveillance is preferable to immediate surgical excision for benign papillomas diagnosed on core needle biopsy.